Production of bispecific monoclonal antibodies recognising both carcinoembryonic antigen (CEA) and doxorubicin - Reddy, Vijay Subba, 1961- (1993)
Thesis (Ph.D.)--Memorial University of Newfoundland, 1993. Medicine Bibliography: leaves 250-275.